2013
DOI: 10.1371/journal.pone.0057965
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Decisions: A Cross-National Study of Treatment Preference Discussions and Surrogate Decision-Maker Appointments

Abstract: BackgroundMaking treatment decisions in anticipation of possible future incapacity is an important part of patient participation in end-of-life decision-making. This study estimates and compares the prevalence of GP-patient end-of-life treatment discussions and patients’ appointment of surrogate decision-makers in Italy, Spain, Belgium and the Netherlands and examines associated factors.MethodsA cross-sectional, retrospective survey was conducted with representative GP networks in four countries. GPs recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 42 publications
6
53
0
7
Order By: Relevance
“…Therefore, we have to address advance care planning in a different way in this population, including earlier discussions about treatment preferences. 16,17 Furthermore, these issues about receiving treatment inappropriately at the EOL are not limited to people with cancer and pervade many other chronic illness populations such as patients with pulmonary, cardiac, or kidney disease. [18][19][20] This study has shown how much time is spent with patients who subsequently are subject to EOL decisions and LOMT and emphasizes that, although not a widely recognized part of the CCOT/MET role or competencies, 9 dealing with EOL care constitutes a significant aspect of the work of CCOTs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have to address advance care planning in a different way in this population, including earlier discussions about treatment preferences. 16,17 Furthermore, these issues about receiving treatment inappropriately at the EOL are not limited to people with cancer and pervade many other chronic illness populations such as patients with pulmonary, cardiac, or kidney disease. [18][19][20] This study has shown how much time is spent with patients who subsequently are subject to EOL decisions and LOMT and emphasizes that, although not a widely recognized part of the CCOT/MET role or competencies, 9 dealing with EOL care constitutes a significant aspect of the work of CCOTs.…”
Section: Discussionmentioning
confidence: 99%
“…18 This phenomenon is not, however, limited to Italy, as ADs are equally scarce in other European countries. 40 However, in Italy, ADs do not have legal force, and the few ADs that patients have created are simply an expression of wish rather than of will…”
Section: Typology Of Critical Decisionsmentioning
confidence: 99%
“…This may be partly related to the frequent lack of legal representatives (guardians) and advanced directives. 16,18 In these cases, the decision-making power of the NH physician is stronger than the influence of the GP on the family of a patient who is cared for at home; decisions for HC patients are more likely to be made jointly by the GP and the patient's family. In the NHs, most CDs were only communicated with family members after they were made, despite the fact that the large majority of our NH patients received family visits every day or several times a day, and the medical staff was present for many hours of the day and during weekends.…”
Section: Typology Of Critical Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to stress the difficulty of organizing an AWD, the importance of specifying preferences and/or constraints on life support treatment, and the possibility that vague or inconsistent language can affect implementation (10) . Still, one of the main cautions against the use of these policies in decision-making at the end of life is that people may not be able to understand different treatment options without being properly informed (11) .…”
Section: Introductionmentioning
confidence: 99%